Calidad de servicio y su influencia en las ventas en tienda Credivargas de la ciudad de Iquitos 2021 - Lozano Bazan, Bruno Anderson (2022)
The objective of this research was to analyze the influence of the quality of service on sales in the Credivargas store in the city of Iquitos 2021, the type of descriptive - correlational, non-experimental and cross-sectional research was used, the population is made up of 340 customers of the Credivargas store in the city of Iquitos, the survey was carried out on a sample of 99 clients of the company, a Pearson correlation value equal to 0.739 was obtained as a result, which indicates a significant and positive correlation of high degree, the value of sigma (two-sided) is 0.000; applying the decision rule, comparing the p-value calculated from the data with the theoretical p-value from Table = 0.05. If the calculated p-value is greater than or equal to 0.05, Ho will be accepted. But, if the calculated p-value is less than 0.05, Ha will be accepted. According to the value obtained, we confirm that the alternative hypothesis is accepted and the null hypothesis is rejected. Then, it is concluded that the quality of service positively influences sales in the Credivargas store in the city of Iquitos 2021.